Música brasileira popular no ensino da trompa: perspectivas e possibilidades formativas. - Feitosa, Radegundis Aranha Tavares (2016)
Research on popular music teaching have gone through development in recent years, gaining, as a result, considerable importance and legitimacy, especially within the context of research in music education. Based on this fact, the present work shows the results of a study on popular music teaching, contemplating most specifically the teaching of the brass instruments in the Brazilian Federal Universities and UNICAMP. This thesis aims to present, to analyze and to discuss about the main didactic materials employed by these teachers on Brazilian popular music teaching to brass instruments, reflecting and pointing guidelines for the insertion of Brazilian popular music on french horn teaching. The research methodology included bibliographical studies, documental research, questionnaires, semi-structured interviews and the empirical experiences consolidated by the author’s expertise both as a performer and a teacher of the instrument at Federal University of Rio Grande do Norte and in other parts of Brazil. The research cleared that the popular music teaching should be developed from parameters adequate to the diversity of manifestations that constitutes this phenomenon on society. It became clear that on Brass instruments teaching formative proposals that contemplate Brazilian popular music are still rare, if compared to the insertion of these instruments on the reality of the studied universities. As a consequence, the main didactic materials are quantitative limited, being more used general proposals related to interpretative dimensions of Brazilian popular music. Having the information collected as a basis, it was possible to understand that the insertion of the popular music on the horn teaching should be done from guidelines that contemplate from the specificities of Brazilian popular music to the singularities of the instrument